2015
DOI: 10.1111/eea.12293
|View full text |Cite
|
Sign up to set email alerts
|

DoesWolbachiainfection affect decision‐making in a parasitic wasp?

Abstract: Various physiological effects of Wolbachia infection have been reported in invertebrates, but the impact of this infection on behavior and the consequences of these behavioral modifications on fitness have rarely been studied. Here, we investigate the effect of Wolbachia infection on the estimation of host nutritive resource quality in a parasitoid wasp. We compare decision-making in uninfected and Wolbachia-infected strains of Trichogramma brassicae Bezdenko (Hymenoptera: Trichogrammatidae) on patches contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 80 publications
(102 reference statements)
2
27
0
Order By: Relevance
“…However, the memory duration of the infected wasps who were able to learn (i.e., who displayed an orientation towards the conditioned odor), was significantly shortened, regardless of the number of training sessions undergone. As our 2 strains had the same genetic background (Kishani Farahani et al ., ), their difference in memory retention should be attributed first to the Wolbachia infection of the infected strain. This reduced memory duration could result from the manipulation of host behavior by Wolbachia , intended to increase Wolbachia transmission.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the memory duration of the infected wasps who were able to learn (i.e., who displayed an orientation towards the conditioned odor), was significantly shortened, regardless of the number of training sessions undergone. As our 2 strains had the same genetic background (Kishani Farahani et al ., ), their difference in memory retention should be attributed first to the Wolbachia infection of the infected strain. This reduced memory duration could result from the manipulation of host behavior by Wolbachia , intended to increase Wolbachia transmission.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, Wolbachia can be transmitted via the superparasitism behavior of their hosts by horizontal transmission (i.e., when a female oviposits into a host that has already been parasitized, the contaminated larvae can transmit the Wolbachia to the other larvae present in the host; Huigens et al, 2000Huigens et al, , 2004. A previous study (Kishani Farahani et al, 2015) has shown that infected females display higher superparasitism rates. As infected wasps produce only female offspring, it would lead to lower genetic diversity among this population in comparison to uninfected populations (Stelzer, 2011;Simon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations